MEDIA PEMBELAJARAN PUZZLE MELALUI PENDEKATAN KONTEKSTUAL PADAANAK TK DI MASA PANDEMI COVID-19: STUDI KASUS DI TK SARASWATI 1 DENPASAR - Adnyani Ni Wayan; Redana Made; Karsana I Nengah (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2021)
Puzzle learning media through an approach contextual during the Civil-19 pandemic as wrong an application of online learning trough WhatsApp group a Google Meet. Media puzzle has many benefits for children at early age is physical and motor training improve children's cognitive development, art, and train children’s creativity through playing while studying. This research was designed with an approach qualitative. Research this aim to describe what are the basics thought context and media intervening conditions puzzle learning trough a contextual approach puzzle through a contextual approach to kindergarten children during the Covid-19 pandemic on learning interactions in kindergarten Saraswati 1 Denpasar. The theory used to analyze the problem is; Piaget's cognitive theory. The data collection method is non-participant observations, semi-structured interviews, library and documentation. Data that has been collected analyzed by descriptive analysis method qualitative data reduction steps, presentation of data, and concluding. The results of the study show (1) the basics thought context and media intervening conditions puzzle learning through a contextual approach in kindergarten children during the covid-19 pandemic in kindergarten Saraswati 1 Denpasar (2) application of the media puzzle learning through a contextual approach in kindergarten children during the Covid-19 pandemic: divided into 3 stages, namely the planning stage, stage implementation, evaluation stage, (3) media impact puzzle learning trough a contextual approach in kindergarten children during the covid-19 pandemic on the interaction of learning methods which is used to play while learning, method Questions and answers at TK Saraswati 1 Denpasar.